The effects of student choice of difficulty of homework on motivation and homework completion - Setz, Keith (My University, 2015)
Research suggests that students often fail to complete homework due to lack of motivation, partly due to the absence of student choice and a mismatch in assignment difficulty and student's ability level. This action research project examined the effect of student choice of homework difficulty on homework completion and motivation. The study included 68 eighth-grade students from a suburban middle school in Southeastern Wisconsin in the fall trimester of the 2014-2015 school year. Two classes were assigned as the experimental group and one class served as the control group. Both groups received the same classroom instruction, but the experimental group was allowed a choice on the difficulty of their homework and the control group was assigned a homework task to complete. Pre- and post-surveys were used and analyzed with a t-test. Results showed significant changes in motivation on two items from the survey. Homework completion percentages were also calculated, but did not show a change in homework completion for either of the groups.
This file was last viewed in Adobe Reader 2015 release.
Keywords: Homework--Psychological aspects; Motivation in education; Mathematics--Study and teaching (Middle school)